Market design a linear programming approach to auctions and matching - Bichler, Martin (Cambridge, United Kingdom Cambridge University Press, 2018)
The digital economy led to many new services where supply is matched with demand for various types of goods and services. More and more people and organizations are now in a position to design market rules that are being implemented in software. The design of markets is challenging as it needs to consider strategic behavior of market participants, psychological factors, and computational problems in order to implement the objectives of a designer. Market models in economics have not lost their importance, but the recent years have led to many new insights and principles for the design of markets, which are beyond traditional economic theory. This book introduces the fundamentals of market design, an engineering field concerned with the design of real-world markets. --Provided by Publisher.
Keywords: Markets -- Mathematical models; Microeconomics -- Textbook